2005
DOI: 10.1007/s11104-004-2695-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-year field response of young olive trees (Olea europaea L., cv. Arbequina) to soil salinity: Trunk growth and leaf ion accumulation

Abstract: Irrigated olive is rapidly increasing in arid and semiarid areas, many of which may be negatively affected by soil salinity. We evaluated changes in trunk growth and leaf Cl ) , Na + and K + concentrations in young Arbequina olives (Olea europaea L.) grown in a saline-sodic field over a three-year period. The trunk diameter was measured at the beginning and the end of the 1999 (70 trees), 2000 (59 trees) and 2001 (42 trees) growing periods. Leaves, sampled in August of each year, were analyzed for Cl ) , Na + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 13 publications
(13 reference statements)
10
35
2
2
Order By: Relevance
“…This mechanism was previously observed in Salvadora oleoides [33]. The uptake of potassium and magnesium did not change based on the different levels of salinity, in agreement with the findings of other authors on different species [12,31,34]. Moreover, the ability of the mastic tree to maintain an adequate selectivity in the uptake of potassium under a saline environment is often associated with salinity tolerance [35].…”
Section: Discussionsupporting
confidence: 89%
“…This mechanism was previously observed in Salvadora oleoides [33]. The uptake of potassium and magnesium did not change based on the different levels of salinity, in agreement with the findings of other authors on different species [12,31,34]. Moreover, the ability of the mastic tree to maintain an adequate selectivity in the uptake of potassium under a saline environment is often associated with salinity tolerance [35].…”
Section: Discussionsupporting
confidence: 89%
“…This upper boundary will represent the limiting response to soil salinity, and variates that fall below the boundary will represent those sites where stress factors other than salinity limit growth (Milne et al 2006). We fitted the maximum ΔRD and Δ i RD observations to soil salinity using the eye-fitting upper-envelope approach that we have previously validated with other quantitative statistical analysis (Aragüés et al 2004) and applied in the study of the field response of olive to soil salinity (Aragüés et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Cl is the principal toxic ion for grapevines growing under saline conditions. Bernstein et al (1969) concluded that leaf Cl levels in excess of 300 mmol kg −1 were injurious in the five studied cultivars. Injury by Cl toxicity in grapevine varies depending on the ability for rootstocks to accumulate Cl and restrict its transport to the shoots (Downton 1977).…”
Section: Introductionmentioning
confidence: 93%
“…They found a negative and significant correlation (r=-0.797 ** ) between the percentages of silt and clay in the soil and olive shoot growth. Melgar et al (2009) indicated that soil salinity did not cause changes in any of the growth variables measured, including shoot length, whereas Aragues et al (2005) found significant decreases in trunk diameter growth with increases in soil salinity.…”
Section: Discussionmentioning
confidence: 92%